CRANK: CLIMATE RESILIENCE WATER TANK WITH RAINWATER HARVESTING AND FILTRATION TECHNOLOGY AS HOUSEHOLD WATER SAFE STORAGE TO TACKLE CLIMATE CHANGE - Diandra, Khansa Allysha; Widyasari, Sherien Sherlita; Zukrianto, Shabrina Arthariani (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Indonesia, a country highly susceptible to climate change, faces severe water scarcity due to unpredictable rainfall patterns and intensified extreme weather events. This paper presents an innovative solution, the Climate Resilience Water Tank with Rainwater Harvesting and Filtration Technology (CRANK), to address the deepening water scarcity crisis amplified by climate change. CRANK is a sustainable water storage system that integrates rainwater harvesting technology with infiltration wells. The system collects rainwater from rooftops, filters it, and stores it in a tank. When the tank reaches its maximum capacity, the excess rainwater is channeled into infiltration wells where it is filtered and replenishes the groundwater table. This dynamic strategy ensures the optimization of rainwater resources based on local weather dynamics. CRANK is a dependable, sustainable water source for various purposes, including drinking, cooking, and agriculture, and can alleviate the burden on pre-existing water supplies. It also mitigates urban flooding risks by efficiently managing surface water runoff. The feasibility of CRANK is meticulously assessed, including cost of production, profit margin, and operational expenditures, making it an affordable and lucrative solution. The system's target implementation sites are remote villages grappling with severe water scarcity. CRANK represents a significant step towards climate change adaptation and resilience by providing a sustainable, climate-resilient remedy for the water scarcity problem in Indonesia.